PRODUKTIVITAS PRIMER FITOPLANKTON DI SUNGAI BETIMUS KABUPATEN DELI SERDANG PROVINSI SUMATERA UTARA Primary Productivity of Phytoplankton in Betimus River Deli Serdang Regency North Sumatra Province - Johannes Keynes Harianja; Hesti Wahyuningsih; Rusdi Leidonald (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2017)
The research about Aquatic Primary Productivity needs to be done, it is because by knowing the value of primary productivity in the waters, will be known fertility waters. The research was done in May 2016. The aim of this research was to knowing the value of Primary Productivity of phytoplankton in Betimus River at Deli Serdang and to analyze its relationship with the physical and chemical factors. The sampling station was determinated by Purposive sampling method. Samples were collected from 3 sampling station. The result showed that of primary productivity range from 100,096-250,240 mg C/m3/day, the highest value was at station 3 and the lowest value was at station 1. Analysis of pearson correlation shows that the factors which have a very strong relationship with the primary productivity are DO, phosphate, nitrate, and the abundance of phytoplankton, factor which has a strong relationship with pimary productivity is temperature, and factor which has a moderate with pimary productivity is pH.Key Words: Primary Productivity, Purposive sampling method, Phytoplankton.